Primitive neuroectodermal tumour of the kidney: An unusual case mimicking renal angiomyolipoma with minimal fat - Xie, Jing; Wen, Jin; Bi, Ya-lan; Li, Han-zhong (Canadian Urological Association Journal, 2015)
Primitive neuroectodermal tumour (PNET) is a highly aggressive neoplasm that develops classically in the central nervous system. PNET of the kidney (rPNET) is extremely rare. Recently, a 23-yearold woman complained of left flank pain and intermittent hematuria for 3 months and was admitted to our hospital. A computed tomography (CT) scan and magnetic resonance imaging demonstrated a 5.1 × 4.4-cm heterogenous mass with unconspicuous reinforcement in the upper pole of the left kidney. F18-FDG positron emission tomography CT (PET-CT) revealed the mass as a benign lesion with internal extensive bleeding. Renal angiomyolipoma with minimal fat was diagnosed. Three months later, a CT scan showed that the mass shrank to 3.1 × 2.6 cm and nephron-sparing surgery of the left kidney was performed at the patient’s request. However, histologic features and immunohistochemical analysis confirmed the diagnosis of rPNET. Five cycles of combined chemotherapy were executed. At the 11-month follow-up, the patient showed no evidence of metastasis or recurrence.